Associations between alcohol outlets and emergency department injury presentations: Effects of distance from the central business district - Hobday, M.; Meuleners, L.; Liang, W.; Gilmore, William; Chikritzhs, T. (2016)
Objective: To examine the effects of licensed outlets and sales on levels of alcohol-related injuries presenting to emergency departments (EDs) in the Inner, Middle and Outer postcode zones of Perth, Australia. Methods: Using panel data (2002–2010), a surrogate measure (based on day of week and time of day of presentation) was used to identify alcohol-related injuries presenting at EDs. Postcodes were grouped according to their distance from the central business district (CBD). Numbers of alcohol outlets and their sales were the primary explanatory variables. Data were analysed using negative binomial regression with random effects. Results: In the Inner and Outer postcode zones, counts of on-site outlets were positively associated with alcohol-related injury (IRR: 1.008; 95%CI 1.003–1.013 and IRR: 1.021; 95%CI 1.013–1.030 respectively). An additional off-site outlet was associated with 6.8% fewer alcohol-related injuries (95%CI 0.887–0.980). In the Middle postcode zone, mean off-site sales were positively associated with injury (IRR: 1.024; 95%CI 1.003–1.044). Conclusions: Associations between alcohol availability variables and injury differed by outlet type and distance from the CBD. Implications: These findings provide further evidence to support stronger controls on liquor licensing, and indicate the need for different controls according to the location and type of licence.